Responses of Modern Broiler Chicks to Stocking Density, Green Tea, Commercial Multi Enzymes and Their Interactions on Productive Performance, Carcass Characteristics, Liver Composition and Plasma Constituents - El-Deek, A.A.; Al-Harthi, M.A. (International Journal of Poultry Science, 2004)
The objective of this work was to study the responses of modern broiler chicks to stocking density, green tea, commercial Multi enzymes (Optizyme® p-5) and their interaction on productive performance, carcass characteristics, chemical composition of liver and plasma constituents. Commercial breeds (Lohman) of broiler chicks were housed at different densities of 10, 14 and 18 bird/m2 during the period from 7 to 43 days of age. Chicks within each density were fed four experimental diets; one of them was used as a control diet. In the other three diets the control diet was supplemented with green tea (5g/kg feed) or Multi enzymes (1 g /kg feed), or mixture of both. Therefore, there were 12 experimental treatments in which each treatment was replicated four times. Results could be summarized as follows: Stocking density had no significant effect on growth of broiler chicks, feed intake and feed conversion ratio (FCR) during 7-43 days of age, except for increasing stocking density of 18 bird/m2 during only the period from 22 to 43 days of age while reduced growth and feed intake significantly. Addition of green tea, Multi enzymes or their mixture had no significant effect on growth, feed intake and FCR of broiler chicks. There were significant interactions among stocking density and feed additives. The best dressing percentage was obtained from group stocked at 14 bird/m2 and fed the control diet. Also, hind part weight and % were the highest of birds stocked at 10/m2 and fed diet supplemented with Multi enzymes or those stocked at 14 bird/m2 and fed the control diet. There was significant interaction between stocking density and feed additives on spleen as absolute or relative weight, showing that the highest weight and % of spleen were obtained of groups fed mixture of Multi enzymes and green tea and stocked at 10 bird/m2, and groups fed diets supplemented with Multi enzymes and stocked at either 14 or 18 bird/m2. Dressing % and hind part weight (g) and (%) decreased significantly as a result of increasing stocking density from 14 to 18 bird/m2, but they were not significantly different from those stocked at 10 bird/m2. Multi enzymes improved absolute weight (g) of front part compared to the control diet, while addition of green tea, Multi enzymes and their mixture improved front part % significantly compared to the control diet. A mixture of green tea and Multi enzymes significantly increased liver%, while Multi enzymes decreased significantly absolute and heart % compared to the control group. A mixture of green tea and Multi enzymes significantly decreased intestinal weight and % compared with the control diet without or with green tea. Stocking density had no significant effect on chemical composition of liver and plasma constituents of broiler chicks as well as liver functions as judged by plasma ALT and AST activities during the experimental period. Green tea had no significant effect on chemical composition of liver and plasma total protein and its fraction, total lipids and cholesterol and plasma AST and ALT activities. In conclusion broiler chicks could be stocked up to 14 bird/m2 without adverse effect on growth performance, while addition of green tea, Multi enzymes or their mixture had no enhancing effect on growth performance of broiler stocked at different densities.